Facing the unknown crimes of older generations: Emotional and cognitive reactions of young Italian students reading an historical text on the colonial invasion of Ethiopia. (January 2018) - Leone, Giovanna; d'Ambrosio, Marialibera; Migliorisi, Stefano; Sessa, Isora
Abstract: When victims are weak and isolated, social denial of crimes committed against them is a banal and often long-lasting phenomenon. Nevertheless, reactions to the breaking of denial on past wrongdoings is a scarcely studied issue. This experimental study explores reactions of forty-two Italian university students, when exposed to historical information on colonial crimes committed by the Italian Army against Ethiopians. Before the experimental task, participants proved to be ignorant of these historical facts, up until now literaly denied in the Italian social discourse. The wording of a same historical text was manipulated in order to describe Italian colonial crimes either clearly (using words as "poisonous gas") or in an implicit way (using words as "unconventional weapons"). When reading the historical text participants were unobtrusively observed. Immediately after reading the text and a week after reading it, participants self-assessed their cognitive and emotional reactions. A week after they self-assessed as well their self-conscious emotions of guilt, moral and social shame, their agreement with reparative actions, and their belief of the widespread social myth (Italiani Brava Gente, i.e. IBG) describing Italian people as good and harmless types . Results showed that 45.2 % of participants expressed primary negative emotions when reading. Participants exposed to the detailed text showed higher negative emotions and a higher level of moral shame. A week after reading, all participants unexpectedly showed a higher belief in IBG. A minority of participants declared to agree with reparative intentions; this agreement was associated with higher moral shame.